AB0104 Serum adipokine (adiponectin, leptin, visfatin, and resistin) levels in patients with rheumatoid arthritis are differentially modulated by disease activity but may not contribute to treatment resistance. (23rd January 2014) - Hong, S.-J.; Song, R.; Lee, S.-H.; Lee, Y.-A.; Yang, H.-I.; Hur, J.-W.; Kim, K.-S.
Abstract : Background: Even though it is well known that adipokines play important roles in the pathogenesis of RA, the in vivo role of adipokines and their association with disease activity is poorly understood. In particular, the modulation of serum adipokines (adiponectin, leptin, resistin, and visfatin) by RA disease activity or type of therapy including disease-modifying antirheumatic drugs (DMARDs) and tumor necrosis factor (TNF)-α blockers should be more elucidated. Objectives: This study aimed to determine if disease activity and type of therapy in patients with rheumatoid arthritis (RA) differentially modulates serum adipokine levels and if pre-therapy adipokine levels contribute to treatment resistance. Methods: Fasting blood samples from 40 patients with RA were collected at baseline and six months after therapeutic treatment with disease-modifying antirheumatic drugs (DMARDs) and/or tumor necrosis factor (TNF)-α blockers. Serum levels of adiponectin, leptin, visfatin, and resistin were measured by ELISA. Results: Baseline adipokine levels were not significantly different between patients with moderate and high disease activity based on Disease Activity Score (DAS) 28. Among adipokines, only adiponectin was significantly increased in patients who responded to DMARD and/or TNF-α blocker therapy based on ACR20 at six months (from 2, 964±1, 237 to 3, 683±1, 511, P <0.01).However, adiponectin levels in non-responders were not significantly increased (3, 192±2, 090 to 3, 222±1, 150). In vitro adipokine expression patterns of human adipocytes in response to inflammatory stimuli were different from those seen in the serum of patients with RA. Conclusions: Adipokine levels (adiponectin, leptin, visfatin, and resistin) are differentially modulated by disease activity and type of therapeutic treatment in patients with RA. Adipokine level may not contribute to therapeutic resistance to DMARD and/or TNF-α blocking agents. References: Trayhurn P, Wood IS: Adipokines: inflammation and the pleiotropic role of white adipose tissue. Br J Nutr 2004, 92(3):347-355. Cansu B, Cansu DU, Kasifoglu T, Gulbas Z, Korkmaz C: Disease-modifying antirheumatic drugs increase serum adiponectin levels in patients with rheumatoid arthritis. J Clin Rheumatol 2011, 17(1):14-17. Disclosure of Interest: None Declared